MEASURING THE IMPORTANT ELEMENT OF DEFECTS IN THE HERITAGE BUILDI - Siti Nor Fatimah Zuraidi; Mohammad Ashraf Abdul Rahman; Zainal Abidin Akasah, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2018)
This study is conducted to measure the importance element of building defects in the heritage building. A survey was conducted to the occupiers in three country of museum areas. The museum area has been identified through the Department of Museum Malaysia and because of the big number of museum, all staff in the museum areas were required to participate in the study to enable the researcher to collect the data concerning defects. Questionnaire has been employed as the data collection instrument and was distributed to the respondents to this study. The result has shown that the important element of defects in the museum areas is high, as the rate of defects for all elements are severe. Such high important element of defects has apparently only affected the aesthetic value of the museum